A non-classical LysR-type transcriptional regulator PA2206 is required for an effective oxidative stress response in Pseudomonas aeruginosa. - Reen, F; Haynes, J; Mooij, M; O'Gara, Fergal (Public Library of Science, 2013)
LysR-type transcriptional regulators (LTTRs) are emerging as key circuit components in regulating microbial stress responses and are implicated in modulating oxidative stress in the human opportunistic pathogen Pseudomonas aeruginosa. The oxidative stress response encapsulates several strategies to overcome the deleterious effects of reactive oxygen species. However, many of the regulatory components and associated molecular mechanisms underpinning this key adaptive response remain to be characterised. Comparative analysis of publically available transcriptomic datasets led to the identification of a novel LTTR, PA2206, whose expression was altered in response to a range of host signals in addition to oxidative stress. PA2206 was found to be required for tolerance to H2O2 in vitro and lethality in vivo in the Zebrafish embryo model of infection. Transcriptomic analysis in the presence of H2O2 showed that PA2206 altered the expression of 58 genes, including a large repertoire of oxidative stress and iron responsive genes, independent of the master regulator of oxidative stress, OxyR. Contrary to the classic mechanism of LysR regulation, PA2206 did not autoregulate its own expression and did not influence expression of adjacent or divergently transcribed genes. The PA2214-15 operon was identified as a direct target of PA2206 with truncated promoter fragments revealing binding to the 5’-ATTGCCTGGGGTTAT-3’ LysR box adjacent to the predicted -35 region. PA2206 also interacted with the pvdS promoter suggesting a global dimension to the PA2206 regulon, and suggests PA2206 is an important regulatory component of P. aeruginosa adaptation during oxidative stress.